Role of magnetic resonance imaging in sinonasal pathology: a review - Swain, Santosh Kumar; Barik, Prerna; Sarangi, Pradosh Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
The last several years have seen a considerable advancement in the treatment of sinonasal diseases. The advent of minimally invasive functional endoscopic sinus surgery has led to an increased understanding of the anatomy and function of the sinonasal region, making previously inaccessible areas safe to operate in. The advancement in imaging of the sinonasal tract has been associated with the evolution of endoscopic sinus surgery. The imaging of sinonasal pathology has progressed from conventional radiographs (plain films) to computed tomography (CT) and magnetic resonance imaging (MRI). Technological advancements in CT and MRI have given a precise differential diagnosis and greater detail about the anatomical extent of sinonasal pathologies. Because the high water content of the inflammatory state causes a markedly enhanced signal on T2-weighted scans, MRI can currently distinguish between retained secretions and inflammatory responses from the mass of the tumor. The invasive lesions affecting the soft tissues outside of the sinonasal region are more easily distinguished by MRI. MRI largely took the position of CT scan for malignant sinonasal lesions due to its superior capacity to distinguish between inflammation and tumor and its increased sensitivity for intracranial extension. MRI can be more useful than a CT scan in demonstrating the degree of soft tissue abnormalities and in identifying lesions that have returned after surgery.